2016
DOI: 10.1016/j.jsxm.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Facilitates Vaginal Lubrication by Activation of Epithelial ATP-Sensitive K+ Channels and Cystic Fibrosis Transmembrane Conductance Regulator

Abstract: Introduction Hydrogen sulfide (H2S) plays a large role in female and male sexual responses characterized by a smooth muscle relaxant effect. Moreover, H2S is a novel pro-secretory neuromodulator that modulates epithelial ion transport. However, whether H2S has a role in regulating vaginal epithelial ion transport and fluid secretion has not been extensively studied. Aim To identify the effects of H2S on vaginal epithelial ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…This hyperpolarises the apical membrane potential and facilitates apical chloride efflux 18,19 . Similar observations were recently reported in a rat vaginal epithelial preparation, where exogenous H 2 S elicits a chloride secretion which involved activation of basolateral ATP-sensitive potassium channels and apical chloride efflux via CFTR 21 . However, the mechanism of how H 2 S might facilitate opening of CFTR remains elusive.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…This hyperpolarises the apical membrane potential and facilitates apical chloride efflux 18,19 . Similar observations were recently reported in a rat vaginal epithelial preparation, where exogenous H 2 S elicits a chloride secretion which involved activation of basolateral ATP-sensitive potassium channels and apical chloride efflux via CFTR 21 . However, the mechanism of how H 2 S might facilitate opening of CFTR remains elusive.…”
Section: Introductionsupporting
confidence: 89%
“…In this study we investigated the regulation of CFTR by H 2 S. Previous studies using the mouse hippocampal cell line HT22 25 or rat vaginal epithelial preparations 21 suggested that CFTR might be a target for H 2 S. In order to elaborate on this hypothesis, human CFTR was heterologously expressed in Xenopus oocytes and functional CFTR expression was confirmed by application of the cAMP-elevating compounds forskolin and IBMX, which resulted in a transient increase in transmembrane currents which did not occur in native, non-injected oocytes. These observations are consistent with previously published functional electrophysiological analyses of human CFTR in Xenopus oocytes 23,26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ферменти синтезу H 2 S наявні в епітелії піхви. Встановлено, що він сприяє вагінальній лубрикації (змащуванню піхви) через вплив на транспорт К + та Clвагінальним епітелієм [63]. H 2 S викликає релаксацію гладеньких м'язів кавернозних тіл пеніса.…”
Section: сигнальна функція сірководнюunclassified